Perbedaan Engagement Tenaga Kesehatan Rumah Sakit Pemerintah dan Rumah Sakit Swasta dalam Pengembangan Pelayanan Kesehatan - Tita Miawati; Junengsih Junengsih (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to identify differences in engagement of health workers in government hospitals and private hospitals to improve the quality of health services in hospitals. The study is a qualitative study with data collection through Forum Group Discussions in two private hospitals and one government hospital. The result of the study found that the level of engagement of health workers in private hospitals was higher than in government hospitals. The study recommends efforts to improve the engagement of health workers in government hospitals, especially in indicators of vigor, loyalty, concern to productivity, loyalty, and absorption by strengthening the implementation of organizational culture in daily activities and improving servant leadership.